The Implementation of Sexual and Reproductive Health Education to Future Bridegrooms: Scoping Review - Machfudloh Machfudloh; Andari Wuri Astuti (Universitas Aisyah Pringsewu, 2022)
Sexual and reproductive health (SRH) is a fundamental health problem that is recognized globally. One of the reproductive and sexual health problems is the lack of sensitivity to reproductive health education for the future bridegroom. It can be the cause of the high Maternal and Child Mortality Rate (MMR and IMR). Sexual and reproductive health education for the future bridegroom is an effort to enhance knowledge with the aim of preventing dissatisfaction and failure in married life. Various challenges in providing sexual and reproductive health education (SRH) such as internal and external factors must be resolved immediately with the support of the relevant policymakers. The purpose of this research was to identify evidence related to sexual and reproductive health education for future bridegrooms. The method in this research was scoping review. The literature search in this study used 3 health journal databases, namely Ebsco, ProQuest, Willey online library, and 1 search engine; Google Scholar. Articles were selected using inclusion criteria, namely original research, in English and Indonesian, published in the last 5 years (2016–2021). The total search results were 2,743 articles, and ten articles were found that met the inclusion criteria in the author's review. The instruments used to assess the quality of articles were the Joana Brigs tool from Joana Brigs Institute (JBI) and the Mixed Methods Appraisal Tool. The results of the review found data related to the need for sexual and reproductive health education for future bridegrooms, barriers, and efforts/evidence-based made both nationally and internationally. From the review of the ten articles that the need for sexual and reproductive health education is not only due to medical problems, but also from the perspective of social problems, the provision of SHR services and government policies is considered a priority.